Trait associations in the pangenome of pigeon pea (Cajanus cajan). Issue 9 (12th March 2020) - Zhao, Junliang; Bayer, Philipp E.; Ruperao, Pradeep; Saxena, Rachit K.; Khan, Aamir W.; Golicz, Agnieszka A.; Nguyen, Henry T.; Batley, Jacqueline; Edwards, David; Varshney, Rajeev K.
Summary: Pigeon pea ( Cajanus cajan ) is an important orphan crop mainly grown by smallholder farmers in India and Africa. Here, we present the first pigeon pea pangenome based on 89 accessions mainly from India and the Philippines, showing that there is significant genetic diversity in Philippine individuals that is not present in Indian individuals. Annotation of variable genes suggests that they are associated with self‐fertilization and response to disease. We identified 225 SNPs associated with nine agronomically important traits over three locations and two different time points, with SNPs associated with genes for transcription factors and kinases. These results will lead the way to an improved pigeon pea breeding programme.